Enhancing drought tolerance in horticultural plants through plant hormones: a strategic coping mechanism - Huang, Shanxia; Jin, Songheng (Frontiers in Plant Science, 2025)
Abiotic stresses are considered as a significant factor restricting horticultural crop productivity and quality. Drought stress is a major environmental constraint among the emerging concerns. Plants have significant susceptibility to drought stress, resulting in a marked decline in production during the last several decades. The development of effective strategies to mitigate drought stress is essential for sustainable agriculture and food security, especially considering the continuous growth of the world population. Several studies suggested that exogenous application of phytohormone to plants can improve drought stress tolerance by activating molecular and physiological defense systems. Phytohormone pretreatment is considered a potential approach for alleviating drought stress in horticultural plants. In addition, melatonin, salicylic acid, jasmonates, strigolactones, brassinosteroids, and gamma-aminobutyric acid are essential phytohormones that function as growth regulators and mitigate the effects of drought stress. These hormones frequently interact with one another to improve the survival of plants in drought-stressed environments. To sum up, this review will predominantly elucidate the role of phytohormones and related mechanisms in drought tolerance across various horticulture crop species.